Always Read the Label: The Identity and Strategy of Britain's 'Christian Right'. (2nd January 2016) - Kettell, Steven
ABSTRACT: In recent years conservative Christian groups in Britain have been involved in a number of high profile and controversial policy issues. This has led some commentators to raise the question of a British 'Christian Right' similar to that which rose to prominence in the United States from the 1970s. What is absent from these debates, however, is an awareness of how identity markers such as 'Christian Right' are shaped and underpinned by the political dynamics of group mobilisation. Utilising insights from Social Identity Theory, and drawing on a series of elite-level interviews, this paper shows that conservative Christian groups reject the 'Christian Right' label, but that this forms part of a broader strategic positioning in response to challenges posed by the pressures of secularisation.